GREECE MILITARIZATION IN AEGEAN ISLAND: AN INTERNATIONAL LAW PERSPECTIVE - Yordan Gunawan; Aldha Febrila; Carissa Shifa Novendra; Siti Asdilla Dzakiyyah (Fakultas Hukum, Universitas Diponegoro, 2023)
In June 2022, President Erdogan of Turkey suspended bilateral contact with Greece, alleging that Greece's militarization of islands in the eastern Aegean Sea violated international law. This issue stems from Greece's decision to militarize an island in the Aegean Sea, which was designated as demilitarized under the Lausanne Peace Treaty. Greece argues that this militarization is necessary for self-defense and conforms to international norms. This research critically examines the status of the demilitarized island under international law and evaluates Greece's justification for self-defense within the framework of global norms. Utilizing normative legal research with a case study approach, the study finds that Greece has indeed breached the terms of the Lausanne Peace Treaty. Furthermore, Greece's claims of self-defense are deemed invalid since they are not qualified meet the criteria under international law. The research concludes by recommending that Turkey pursue legal recourse, potentially through the International Court of Justice, to address this breach. This approach aims to uphold the principles of international agreements and seek resolution through established legal mechanisms.